Step-Wise Ethanol Adaptation Drives Cell-Wall Remodeling and Rom2/Knr4 Activation in Brettanomyces Bruxellensis - Ganga-Munoz, M; González-Poblete, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Brettanomyces bruxellensis has been described as the main spoilage microorganism in wines due to its ability to produce volatile phenols, which negatively impact the final product’s organoleptic properties. This yeast can grow and survive in environments that are too nutritionally poor and stressful for other microorganisms, and one of the stressful conditions it can endure is the high alcohol content in wine. In this study, cell wall morphology and the expression of some genes related to its composition were characterized under increasing ethanol concentrations to establish a possible ethanol resistance mechanism. B. bruxellensis LAMAP2480 showed greater resistance to β-1,3-glucanase activity when grown in media supplemented with 5% or 10% ethanol compared with the control assay (without ethanol). Transmission electron microscopy showed no significant differences in cell wall thickness during the different adaptation stages. However, the amount of wall polysaccharides and chitin briefly increased at 1% ethanol but returned to baseline at 5% and 10%. The amount of wall-associated protein increased progressively with each increment in ethanol concentration. In addition, overexpression of the ROM2 and KNR4/SMI1 genes was observed at 10% ethanol. These results suggest that the integrity of the cell wall might play an important role in the adaptation of B. bruxellensis to an ethanol-containing medium. © 2025 by the authors.